The Role of Price in Deciding to Purchase Ready-to-Drink Tea - Arissetyanto Nugroho (Jurnal Manajemen, 2018)
The purpose of this research is to test the factors that influence the decision to purchase The Pucuk Harum tea. There are three variables tested: brand image, price and product quality. The questionnaire was delivered to 100 @pucukharumid consumers and bootstrapped for a 500 data sample. The findings support that all factors, i.e. brand image, price and product quality, significantly influence the decision to purchase The Pucuk Harum. The most important factor is the price, and the factor that had the least influence is image. Smart PLS Simultaneous Equation Modelling was conducted to measure the indirect relationship between fourpaths within the model. The results show that the strongest path is the process of prices that affect the image through the product quality. The price is also an antecedent factor that mostly influences the purchase decision through other variables within the model.